Evaluative Inquiry for Systemic Change: A Guide to Shift Beyond Fixes to Lasting Value - Gates, Emily F.; Vidueira, Pablo (SAGE Publications, Inc, 2025)
In a world where social, ecological, health, and other problems are influenced by multiple, intersecting systems, why do most interventions target single-factor solutions? Why does so much evaluation settle for incremental change, and how could it contribute instead to deeper, lasting, transformative change? Authors Emily F. Gates and Pablo Vidueira make two interconnected arguments in this book: they critique the "fixed" approach of traditional program evaluation and policy analysis, and they advance an alternative approach centered on changing systems and developing the value of efforts toward change. They demonstrate that systemic change that embeds evaluative inquiry is a theoretically supported, practical way to work toward fundamental social change with lasting impact.

Evaluation handbook: 2025 edition - Directorate-General for International Partnerships (European Commission); Hassnain, Hur; McHugh, Karen; Lorenzoni, Marco; Alvarez, Valentin; Augustyn, Anna Maria; Davies, Rick; Rogers, Patricia; Buchanan-Smith, Margie (Publications Office of the European Union, 2025)
The Evaluation Handbook – 2025 Edition reflects the European Commission’s steadfast commitment to promoting a culture of results, accountability, and learning across the EU’s external action. As one of the world’s leading development and international cooperation actors, the European Commission bears a particular responsibility to ensure that its interventions are informed by robust evidence, deliver tangible results, and represent the highest standards of transparency and effectiveness in the use of public funds. Building on the foundations laid by the 2024 edition— which itself constituted a major revision of the 2006 Methodology Guidance—the 2025 edition reflects the continuous evolution of the European Commission’s evaluation practice over the past two decades. It draws on international best practices, incorporates state-of-the-art methodological advances, and acknowledges the increasingly multifaceted nature of development cooperation. This Handbook is attuned to the dynamic policy, institutional, and geopolitical environment in which EU external action operates, offering an adaptive and forward-looking framework to support high-quality evaluations that are both credible and consequential. This Handbook reaffirms evaluation as an indispensable pillar of the EU’s commitment to better regulation, performance-based management, and evidence-informed decision-making. It provides practical and strategic guidance to support evaluation managers, partners, and stakeholders in navigating the full evaluation cycle—from design and implementation to dissemination and uptake of findings.
Keywords: EU action; International policy; aid evaluation; cooperation policy; coordination of aid; development aid; food security; report; the EU's international role; user guide

Relationality: How Moving from Transactional to Transformational Relationships Can Reshape Our Lonely World - Jay, David (North Atlantic Books, 2024)
How moving from transactional to transformational relationships and organizations can save our democracy, nurture our connections, and make us happier and healthier. Powerful institutions, from schools to tech and social media companies, create breeding grounds for isolation by failing to invest in relational work. This obstacle stands in the way of our fight for racial equity, economic justice, and climate resilience. In Relationality, leading asexuality and relationship activist David Jay brings clarity to the crisis with a fresh perspective that expands upon the fundamental idea that all entities in the universe are connected. Jay draws from a range of vivid personal experiences, including his time spent helping tech workers and policymakers reform social media. This book is for people who believe in the power of relationships and want to see increased investment in relational work. Its scientifically grounded framework will help readers foster conversations about relational work, establish conditions for relationships to thrive, and quantify the impact of them. Equipping professionals and activists involved in nonprofit, political, and other types of relational work with the knowledge they need to fight for and utilize resources, Relationality shares valuable insight on: - The history of why institutions fail to invest in relationships - Reimagining ROI calculations to account for relational work - Using tools of prediction and emergence theory to build communities - How stories and data about relationships can help us direct resources toward relational work - Relational economics and the redistribution of wealth With isolation and loneliness on the rise in a post-lockdown world, Relationality offers a roadmap to nourish our connections toward a better, more liberated world—personally, organizationally, and in community.

Theories of Change in Reality: Strengths, Limitations and Future Directions - Koleros, Andrew; Adrien, Marie-Hélène; Tyrrell, Tony (Routledge, 2024)
For over 50 years, evaluators have used theories of change to articulate the causal logic underpinning how an intervention is intended to bring about a desired change. From its origins in programme evaluation, the approach has been adopted more widely for purposes from program design to program management. As theories of change continue to be used for multiple purposes, it is an opportune moment for the evaluation community—where the approach originated—to provide their perspective on the strengths and limitations of the approach and its future directions. To provide these perspectives, we asked nearly 30 of the world’s leading evaluators and programme theorists to provide a short essay on the past, present, and future of theories of change. This book presents their insights organized into five main themes: the use of theories of change in broader public policy contexts; using theories of change to establish causality; developing theories of change reflective of multiple stakeholder perspectives; using theories of change to understand wider societal change processes; and applying theories of change approaches for multiple purposes. By sharing these diverse perspectives, the book aims to both provide evaluators and emerging programme theorists with critical perspectives to inform future practice. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.

Reflecting Forewords - Chambers, Robert; Lewin, Tessa (Practical Action Publishing, 2024)
Reflecting Forewords is an unashamedly ambitious book. Full of lessons from the past that are relevant for the future, it is a compilation of inspiring forewords from books written by Robert Chambers; one of the most influential and prolific scholars to write about participation, poverty, and knowledge in development studies. Tessa Lewin, Robert’s colleague and an experienced practitioner and researcher, has worked with Robert to weave together the forewords alongside a series of reflections from other practitioners and scholars in the field. In our world of dramatic unforeseeable change, Reflecting Forewords seeks to draw lessons and present insights that should not be ephemeral, but can contribute on a lasting way to policy, practice and research in the rest of our 21st century. Readers will draw their own conclusions. The orientation is forward-looking into our unpredictable future, stressing the need to be alert, in touch, nimble, and guided by reflexivity. This curated collection of resurfaced gems will inspire development professionals, teachers and graduate students of development studies, policymakers, historians of development thinking and practice, activists, and all those who are concerned with a better life for all.

Critical systems thinking: a practitioner's guide - Jackson, Michael C. (Wiley, 2024)
"Critical systems thinking is a multiperspectival and multimethodological approach to complex problems that takes advantage of the variety of systems approaches, aware of their different strengths and weaknesses"--
Keywords: Leadership; System analysis; System theory

Co-Intelligence: Living and Working with AI - Mollick, Ethan (WH Allen, 2024)
**A New York Times Bestseller**'Co-Intelligence is the very best book I know about the ins, outs, and ethics of generative AI. Drop everything and read it cover to cover NOW' Angela DuckworthConsumer AI has arrived. And with it, inescapable upheaval as we grapple with what it means for our jobs, lives and the future of humanity.Cutting through the noise of AI evangelists and AI doom-mongers, Wharton professor Ethan Mollick has become one of the most prominent and provocative explainers of AI, focusing on the practical aspects of how these new tools for thought can transform our world. In Co-Intelligence, he urges us to engage with AI as co-worker, co-teacher and coach. Wide ranging, hugely thought-provoking and optimistic, Co-Intelligence reveals the promise and power of this new era.

Scaling Up Development Impact - Guerrero, Isabel; Gokhale, Siddhant; Fahsbender, Jossie (Bowker, 2023)
Today, nearly one billion people lack electricity, over three billion lack clean water, and 750 million lack basic literacy skills. Many of these challenges could be solved with existing solutions, and technology enables us to reach the last mile like never before. Yet, few solutions attain the necessary scale to match the size of these challenges. Scaling Up Development Impact offers an analytical framework, a set of practical tools, and adaptive evaluation techniques to accompany the scaling process. It presents rich organizational experiences that showcase real-world journeys toward increased impact. From the people from IMAGOgg.org

Hidden Potential: The Science of Achieving Greater Things - Grant, Adam (WH Allen, 2023)
#1 New York Times bestseller "This brilliant book will shatter your assumptions about what it takes to improve and succeed. I wish I could go back in time and gift it to my younger self. It would've helped me find a more joyful path to progress."-Serena Williams, 23-time Grand Slam singles tennis championThe #1 New York Times bestselling author of Think Again illuminates how we can elevate ourselves and others to unexpected heights.We live in a world that’s obsessed with talent. We celebrate gifted students in school, natural athletes in sports, and child prodigies in music. But admiring people who start out with innate advantages leads us to overlook the distances we ourselves can travel. We can all improve at improving. And when opportunity doesn’t knock, there are ways to build a door.Hidden Potential offers a new framework for raising aspirations and exceeding expectations. Adam Grant weaves together groundbreaking evidence, surprising insights, and vivid storytelling that takes us from the classroom to the boardroom, the playground to the Olympics, and underground to outer space. He shows that progress depends less on how hard you work than how well you learn. Growth is not about the genius you possess – it’s about the character you develop. Grant explores how to build the character skills and motivational structures to realize our own potential, and how to design systems that create opportunities for those who have been underrated and overlooked.This book reveals how anyone can rise to achieve greater things. The true measure of your potential is not the height of the peak you’ve reached, but how far you’ve climbed to get there.

Foreign Aid and Its Unintended Consequences - Koch, Dirk-Jan (Routledge, 2023)
Foreign aid and international development frequently bring with it a range of unintended consequences, both negative and positive. This book delves into these consequences, providing a fresh and comprehensive guide to understanding and addressing them. The book starts by laying out a theoretical framework based on complexity thinking, before going on to explore the ten most prevalent kinds of unintended effects of foreign aid: backlash effects, conflict effects, migration and resettlement effects, price effects, marginalization effects, behavioural effects, negative spillover effects, governance effects, environmental effects, and ripple effects. Each chapter revolves around a set of concrete case studies, analysing the mechanisms underpinning the unintended effects and proposing ways in which policymakers, practitioners, and evaluators can tackle negative side effects and maximize positive side effects. The book also includes personal testimonies, a succinct overview of unintended effects, and suggestions for further reading. Providing a clear overview of what side effects to anticipate when planning, executing, and evaluating aid, this book will be an important resource for students, development practitioners, and policymakers alike.

The Last 10 Per Cent: Why the World Needs a Leaner, More Innovative and Pragmatic Development Sector, Today - Harper, Erica (Routledge India, 2023)
Criticism that the development sector has not delivered in terms of eliminating extreme poverty, fast-tracking growth and preventing conflict, is neither new nor surprising. In fact, it may be the one thing that scholars, donors and practitioners agree on. While many of these concerns are valid, this book makes a case that the sector is closer to unlocking the gates to more effective and efficient development outcomes than is popularly believed. Specifically, it argues that by overturning a few myths, making better use of evidence and employing some different rules, practitioners, policy specialists and donors can foster the changes in the development architecture that are needed to reach the 10 percent of the world’s population still living in extreme poverty.Engaging, provocative and clear sighted, the book provides insight into interventions around democratic governance, refugee response, counterterrorism, gender mainstreaming, environmental protection and private sector engagement. It is instructive reading for professionals across the development sector, think tanks and NGOs.

The Big Con: How the Consulting Industry Weakens our Businesses, Infantilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry and the way business and government are managed today which must change.Mariana Mazzucato and Rosie Collington show that our economies' reliance on companies such as McKinsey, Boston Consulting Group, Bain & Company, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporate and political accountability and impedes our collective mission of halting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and risk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of modern capitalism, from financialization and privatization to the climate crisis. It is possible because of the unique power that big consultancies wield through extensive contracts and networks - as advisors, legitimators and outsourcers - and the illusion that they are objective sources of expertise and capacity. To make matters worse, our best and brightest graduates are often redirected away from public service into consulting. In all these ways, the Big Con weakens our businesses, infantilizes our governments and warps our economies.Mazzucato and Collington expertly debunk the myth that consultancies always add value to the economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations and communities, and for a new system in which public and private sectors work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Don't Lead Alone: Think Like a System, Act Like a Network, Lead Like a Movement! - Justis, Cleveland; Student, Daniel (Fast Company Press, 2023)
Think. Act. Lead.It seems simple enough. But understanding your desired impact and how it fits into a larger picture, connecting your work to others and finding new collaborators, and bringing those collaborators together and moving them in a unified direction is never easy.Governments, businesses, and nonprofits all have unique approaches and ideas that many of us learn through our work. Yet, we rarely consider the skills needed to create and maintain the partnerships between them. Most of us learn those skills through trial, error, and often, failure. Worse, we typically stay in our self-reinforcing silos, sharing perspectives and frustrations with like-minded people, limiting our vision of what our work can become. By partnering with other sectors, we combine and adapt approaches to solve complex problems, and leaders in any industry can create large-scale change.Cleveland Justis and Daniel Student share a road map for effective partnerships that increase impact and profitability. Using real-life examples and practice exercises, the authors teach how to acquire and use skills to solve complex problems and propel your organization forward by combining a multitude of perspectives, split into three sections:Think Like a SystemAct Like a NetworkLead Like a MovementIt’s time to get out of our silos. Don’t lead alone.

Guide to Principles of Emergent Learning - Darling, Edited Marilyn; Eenigenburg, Avery (The Emergent Learning Community Project, 2023)

The Mom Test: How to talk to customers & learn if your business is a good idea when everyone is lying to you - Fitzpatrick, Rob (CreateSpace Independent Publishing Platform, 2023)
The Mom Test is a quick, practical guide that will save you time, money, and heartbreak.They say you shouldn't ask your mom whether your business is a good idea, because she loves you and will lie to you. This is technically true, but it misses the point. You shouldn't ask anyone if your business is a good idea. It's a bad question and everyone will lie to you at least a little . As a matter of fact, it's not their responsibility to tell you the truth. It's your responsibility to find it and it's worth doing right .Talking to customers is one of the foundational skills of both Customer Development and Lean Startup. We all know we're supposed to do it, but nobody seems willing to admit that it's easy to screw up and hard to do right. This book is going to show you how customer conversations go wrong and how you can do better.

Development Delusions and Contradictions: An Anatomy of the Foreign Aid Industry - Sims, David (Palgrave Macmillan, 2022)
This book analyses the shortcomings of the Western development aid programme. Through exploring the evolution of aid over more than seven decades, development is examined as an industry with a variety of motives and actors. The driving forces and dynamics in the relationship between aid and economic development are highlighted in relation to faulty development structures and misaligned aims. With a particular focus on Egypt, radical questions are posed on how global aid and development can be improved, including how it can respond to the COVID-19 pandemic.This book aims to present an alternative aid framework to help overcome the dysfunctionality of the current international development system. It will be of interest to researchers and policymakers working within development economics and development policy.

The Learning Power of Listening - Guijt, Irene; Gottret, Maria Veronica; Hanchar, Anna; Deprez, Steff; Muckenhirn, Rita (PRACTICAL ACTION PUBLISHING, 2022)
Steff had the pleasure to co-author the first SenseMaker Practitioner Guide with a group of friends and colleagues supported and published by Oxfam and CRS. This practical guide is for those who wish to use SenseMaker to conduct assessments, monitor progress, and undertake evaluations or research. Drawing on more than a decade of experience, the authors share dozens of examples from international development, providing practical tips and ideas for context-specific adaptations. They show how the method can be used to for difficult-to-measure outcomes related to poverty reduction, social justice, peacebuilding, resilience, gender norms, behavior change, governance and environmental management. ​ SenseMaker is a unique participatory method of inquiry that encourages and enables novel insights not obtained from conventional quantitative and quantitative and qualitative methods. It is action-oriented and, therefore, well-suited for people needing data- informed insights for adaptive management. "Writing this guide together with Irene, Veronica, Anna and Rita was an enormous learning process in itself and has further shaped our thinking and practice. We hope it will support first-time and experienced users to enhance their practice and that it will inspire people to explore and innovate further with the method."

Gambling on Development: Why Some Countries Win and Others Lose - Dercon, Stefan (C Hurst & Co Publishers Ltd, 2022)

Lives Amid Violence: Transforming Development in the Wake of Conflict - Schomerus, Mareike (2022)
Violent conflict and its aftermath are pressing problems, particularly for international development initiatives. However, the results of development in conflict contexts have generally been disappointing and their preventative potential thus questionable. Available Open Access, Lives Amid Violence argues that this is because practitioners adhere to a mental model that emphasises linearity, certainty, and causality, assuming that violence is best addressed through work plans that deliver state-building, stabilisation and services. Based on ten years of multi-method research from, in, and on conflict-affected countries, this book challenges this approach.Drawing on a significant collaborative body of scholarship, this work puts forward original and generalizable conclusions about how lives amid violence persist, offering an invitation to abandon restricting mental models and to embrace creative ways of thinking and working. These include paying attention to the long-term effects of conflict on individual behaviour and decision-making, the social realities of economic life, the role service delivery plays in negotiations between citizens and states, and to creating meaningful relationships. Transformation also requires reflection and therefore the book concludes with constructive suggestions on how to practice these insights to better support those whose lives are shaped by violence.More details are available at www.transformingdevelopment.orgThe eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.

Inclusive participatory approaches: A facilitator’s guide - Zaremba, Haley; Elias, Marlène; Devi, J. Tulasi; Priyadarshini, Pratiti (2021)
In community engagement and participatory processes, facilitators must make intentional efforts and adopt inclusive strategies to include marginalized and frequently overlooked groups. Yet, there is a lack of guidance on how to inclusively facilitate participatory processes. Facilitators are therefore often poorly prepared to engage with the power relations that underlie these processes, including those between the facilitator and participants and among participants themselves. This guide addresses this shortcoming by presenting strategies that have been shown to enhance the meaningful participation of women and marginalized groups in participatory processes. The aim is to equip facilitators with tools to create inclusive participatory spaces and community engagement. Although it refers to processes related to natural resource management, the guide is also applicable to the facilitation of participatory processes focusing on other issues or fields of significance to communities.

The Art of Agile Development - Shore, James; Warden, Shane (O'Reilly Media, 2021)
Most companies developing software employ something they call "Agile." But there's widespread misunderstanding of what Agile is and how to use it. If you want to improve your software development team's agility, this comprehensive guidebook's clear, concrete, and detailed guidance explains what to do and why, and when to make trade-offs. In this thorough update of the classic Agile how-to guide, James Shore provides no-nonsense advice on Agile adoption, planning, development, delivery, and management taken from over two decades of Agile experience. He brings the latest ideas from Extreme Programming, Scrum, Lean, DevOps, and more into a cohesive whole. Learn how to successfully bring Agile development to your team and organization--or discover why Agile might not be for you. This book explains how to: Improve agility: create the conditions necessary for Agile to succeed and scale in your organization Focus on value: work as a team, understand priorities, provide visibility, and improve continuously Deliver software reliably: share ownership, decrease development costs, evolve designs, and deploy continuously Optimize value: take ownership of product plans, budgets, and experiments--and produce market-leading software

The Systems Work of Social Change: How to Harness Connection, Context, and Power to Cultivate Deep and Enduring Change - Rayner, Cynthia; Bonnici, François (OUP Oxford, 2021)
The issues of poverty, inequality, racial justice, and climate change have never been more pressing or paralyzing. Current approaches to social change, which rely on industrial models of production and power to "solve" social problems, are not helping. In fact, they are designed to entrench the status quo. In The Systems Work of Social Change, Cynthia Rayner and François Bonnici draw on two hundred years of history and a treasure trove of stories of committed social changemakers to uncover principles and practices for social change that radically depart from these approaches. Rather than delivering "solutions," these principles and practices focus on the process of change itself. Through rich storytelling and lucid analysis, Rayner and Bonnici show that connection, context, and power sit at the heart of the change process, ensuring broader agency for people and communities to create social systems that are responsive and representative in a rapidly changing world. Simple yet profound, this book distills a timely set of lessons for practitioners, leaders, scholars, and policymakers.

PDIA in action - Andrews, Matt; Samji, Salimah (Center for International Development, Harvard University, 2021)
Learning from our experience in 2020, we asked the alumni of our HKS Implementing Public Policy (IPP) Executive Education program, if they wanted to work with our students on their nominated problems. Eight IPP alumni, William Keith Young, Adaeze Oreh, Milzy Carrasco, Kevin Schilling, Artem Shaipov, George Imbenzi, David Wuyep, and Raphael Kenigsberg, who had been trained on PDIA and implementation, signed up to work with our students. Thirty-seven students signed up to take the course beginning January 26th, 2021. The students worked across eight teams and adopted a problem driven approach to foster learning that could help their authorizers develop an action learning strategy to their nominated challenge. This book highlights the students’ work drawing from their blogs as well as the event series. There are 8 sections, one for each of the teams and the problems they worked on during the course. We hope you enjoy reading their stories! Scan the QR Code at the end of each section to learn more.

Applying Evaluation Criteria Thoughtfully - OECD (OECD, 2021)
Relevance, coherence, effectiveness, efficiency, impact, and sustainability are widely used evaluation criteria, particularly in international development co-operation. They help to determine the merit or worth of various interventions, such as strategies, policies, programmes or projects. This guidance aims to help evaluators and others to better understand those criteria, and improve their use. It starts by describing what they are, and how they are meant to be used. Then the definitions and concepts underpinning each criterion are explained. Finally, examples provide the reader with concrete ideas for using them. The criteria were originally laid out in the early 2000s by the Network on Development Evaluation (EvalNet) of the OECD Development Assistance Committee (DAC). Although they have been widely used in evaluation, and beyond, this document is the first to comprehensively explore the concepts in detail, explain their intended use and offer practical guidance. It captures current thinking and best practice in evaluation, drawing on the inputs of internationally renowned evaluation experts from EvalNet and beyond.

Change: How to Make Big Things Happen - Centola, Damon (Little, Brown Spark, 2021)
How to create the change you want to see in the world using the paradigm-busting ideas in this "utterly fascinating" (Adam Grant) big-idea book.​ Most of what we know about how ideas spread comes from bestselling authors who give us a compelling picture of a world, in which "influencers" are king, "sticky" ideas "go viral," and good behavior is "nudged" forward. The problem is that the world they describe is a world where information spreads, but beliefs and behaviors stay the same. When it comes to lasting change in what we think or the way we live, the dynamics are beliefs and behaviors are not transmitted from person to person in the simple way that a virus is. The real story of social change is more complex. When we are exposed to a new idea, our social networks guide our responses in striking and surprising ways. Drawing on deep-yet-accessible research and fascinating examples from the spread of coronavirus to the success of the Black Lives Matter movement, the failure of Google+, and the rise of political polarization, Change presents groundbreaking and paradigm-shifting new science for understanding what drives change, and how we can change the world around us.

Co-creating Digital Public Services for an Ageing Society: Evidence for User-centric Design - Jarke, Juliane (Public Administration and Information Technology, 2021)
This open access book attends to the co-creation of digital public services for ageing societies. Increasingly public services are provided in digital form; their uptake however remains well below expectations. In particular, amongst older adults the need for public services is high, while at the same time the uptake of digital services is lower than the population average. One of the reasons is that many digital public services (or e-services) do not respond well to the life worlds, use contexts and use practices of its target audiences. This book argues that when older adults are involved in the process of identifying, conceptualising, and designing digital public services, these services become more relevant and meaningful.The book describes and compares three co-creation projects that were conducted in two European cities, Bremen and Zaragoza, as part of a larger EU-funded innovation project. The first part of the book traces the origins of co-creation to three distinct domains, in which co-creation has become an equally important approach with different understandings of what it is and entails: (1) the co-production of public services, (2) the co-design of information systems and (3) the civic use of open data. The second part of the book analyses how decisions about a co-creation project’s governance structure, its scope of action, its choice of methods, its alignment with strategic policies and its embedding in existing public information infrastructures impact on the process and its results. The final part of the book identifies key challenges to co-creation and provides a more general assessment of what co-creation may achieve, where the most promising areas of application may be and where it probably does not match with the contingent requirements of digital public services. Contributing to current discourses on digital citizenship in ageing societies and user-centric design, this book is useful for researchers and practitioners interested in co-creation, public sector innovation, open government, ageing and digital technologies, citizen engagement and civic participation in socio-technical innovation.

How Artifacts Afford: The Power and Politics of Everyday Things - Davis, Jenny L. (MIT Press, 2020)
Technologies are intrinsically social. They reflect human values and affect human behavior. The social dynamics of technology materialize through design features that shape how a technology functions and to what effect. The shaping effects of technology are represented in scholarly fields by the concept of “affordances.” Affordances are the ways design features enable and constrain user engagement and social action. This has been a central construct for designers and technology theorists since foundational statements on the topic from JJ Gibson and Don Norman in the 1970s and 80s. With the rise of digitization and widespread automation, “affordance” has entered common parlance and resurged within academic discourse and debate. Davis provides a conceptual update on affordance theory along with a cogent scaffold that shifts the orienting question from what technologies afford, to how technologies afford, for whom, and under what circumstances? “How Artifacts Afford” introduces the mechanisms and conditions framework of affordances in which technologies request, demand, encourage, discourage, refuse, and allow social action, varying across subjects and circumstances. Underlying this mechanisms and conditions framework is a sharp focus on the politics and power encoded in sociotechnical systems. In this timely theoretical reboot, Davis brings clarity to the affordance concept, situates the concept within a broader history of technology studies, and demonstrates how the mechanisms and conditions framework can serve as a transferrable tool of inquiry, critique, and (re)design.

The Politics of Uncertainty : Challenges of Transformation - Scoones, Ian; Stirling, Andy; Stirling, Andy (Routledge, 2020)
Why is uncertainty so important to politics today? To explore the underlying reasons, issues and challenges, this book’s chapters address finance and banking,

Innovation for Development Impact: Lessons from the OECD Development Assistance Committee - OECD (The Development Dimension, 2020)
The development co-operation community needs to innovate to meet the global challenges ahead. Although it has an established track record for innovating partnerships, funding instruments and technologies, they are not enough to deliver the Sustainable Development Goals. This report synthesises the lessons emerging from an OECD Development Assistance Committee peer learning exercise on how innovation efforts can be strengthened, individually and collectively, to achieve the 2030 Agenda. The report is organised around three blocks – strategy, management and culture; organisation and collaboration; and, the innovation process – and provides recommendations on how innovation can best benefit poor and vulnerable people around the world.

Software Engineering at Google: Lessons Learned from Programming Over Time - Winters, Titus; Manshreck, Tom; Wright, Hyrum (O'Reilly Media, 2020)
Today, software engineers need to know not only how to program effectively but also how to develop proper engineering practices to make their codebase sustainable and healthy. This book emphasizes this difference between programming and software engineering. How can software engineers manage a living codebase that evolves and responds to changing requirements and demands over the length of its life? Based on their experience at Google, software engineers Titus Winters and Hyrum Wright, along with technical writer Tom Manshreck, present a candid and insightful look at how some of the world's leading practitioners construct and maintain software. This book covers Google's unique engineering culture, processes, and tools and how these aspects contribute to the effectiveness of an engineering organization. You'll explore three fundamental principles that software organizations should keep in mind when designing, architecting, writing, and maintaining code: How time affects the sustainability of software and how to make your code resilient over time How scale affects the viability of software practices within an engineering organization What trade-offs a typical engineer needs to make when evaluating design and development decisions

Thinking and Working Politically in development - Coalitions for Change in The Philippines - Sidel, John T.; Faustino, Jaime (The Asia Foundation, 2020)
The Asia Foundation and the Australian Embassy in the Philippines today released a new publication, Thinking and Working Politically in Development: Coalitions for Change in the Philippines. Written by London School of Economics and Political Science Professor John T. Sidel and The Asia Foundation’s Jaime Faustino, the book examines the first phase of the Coalitions for Change program (2012-2018) and the contributions to key development policy reforms in the Philippines. The book is a rigorous treatment of the Coalitions for Change program’s transformative policy reforms—alongside lessons from its failures—across diverse policy arenas and in a wide variety of cities and provinces. The chapters are organized thematically: excise tax reform (Chapter 2), land governance reform (Chapter 3), education (Chapter 4), electoral reform (Chapter 5), disaster risk reduction and management (Chapter 6), and subnational governance reform and conflict resolution in Mindanao (Chapter 7). The co-authors together combine an independent, academic perspective on the program’s impacts (Sidel) with a front-row view of doing policy reform in the Philippines – both its political and technical dimensions (Faustino). Based on the empirical research and comparative analysis undertaken by the authors, the book articulates – and substantiates – a strong set of arguments that help to explain the program’s mixed pattern of achievements and disappointments. Overall, the book concludes that the seven-year program achieved significant and sustainable impact using problem-driven, adaptive, and iterative approaches to developmental change. The authors assert the program was at the forefront of notable development approaches: aid effectiveness and development around thinking and working politically, doing development differently, and adaptive programming. Graham Teskey, an early advocate of ‘thinking and working politically’ explores how development agencies can replicate the conditions for success in his Afterword. With illustrative case studies and analyses, the book provides valuable lessons for policymakers, scholars, bilateral agencies, think-tanks, and anyone interested in successfully maneuvering the shifting dimensions of development in the Philippines and elsewhere.

How to design and plan public engagement processes: a handbook - Faulkner, Wendy; Bynner, Claire (What Works Scotland, 2020)
There is a growing hunger for more, and more meaningful, citizen participation in decisions that affect our lives. Across the world, calls for open government, workplace democracy, community empowerment are gaining support, as are innovative developments in deliberative democracy. The current COVID-19 pandemic makes these calls more pressing than ever, given the deepening inequalities it has caused and the complex challenges of building a progressive road out of the crisis. So, now more than ever we need people capable of designing and planning public engagement processes that are empowering and worthwhile. Experienced practitioners know that, without considerable forethought, care and preparation, public engagement processes risk achieving little or, worse, alienating people so that they never engage (with you or anyone else) again. This Handbook seeks to deepen people’s skills in designing and planning effective public engagement processes, by providing a structured four-stage framework for tackling the task. It draws on the authors’ extensive practical experience of training and working with public engagement facilitators across sectors as well as international expertise. You may be a citizen, a community or public engagement practitioner, an elected or government representative, or some other sponsoring organisation or stakeholder. You may be new to this kind of work or experienced but wanting to review and improve your practice. Or you may be studying public participation in democratic processes. Wherever you are coming from, and whatever type of public engagement you are doing, this Handbook promises to be a useful addition to your toolbox.

Evaluation of International Development Interventions: An Overview of Approaches and Methods - Vaessen, Jos; Lemire, Sebastian; Befani, Barbara (World Bank, 2020)
This guide provides an introductory overview of a range of methods that have been selected for their actual and potential use in the field of international development evaluation. For each method, a detailed guidance note presents the method’s main features and procedural steps, key advantages and disadvantages, as well as its applicability. Each guidance note includes references for relevant background readings (basic and advanced) as well as references to other additional resources of interest. Both the choice of approaches and methods and the associated guidance are by no means definitive. IEG plans to periodically update the guide as evaluation practices evolve.